Epidemiology and etiology of Neofabraea species causing lenticel decay of pome fruit in the Western Cape of South Africa - Rochefort, Jessica (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2015.